Estradiol improves behavior in FAD transgenic mice that express APOE3 but not APOE4 after ovariectomy - Balu, Deebika; Valencia-Olvera, Ana C.; Deshpande, Ashwini; Narayanam, Saharsh; Konasani, Sravya; Pattisapu, Shreya; York, Jason M.; Thatcher, Gregory R. J.; LaDu, Mary Jo; Tai, Leon M. (Frontiers in Endocrinology, 2024)
Increasing evidence suggests that females have a higher Alzheimer's disease (AD) risk associated with post-menopausal loss of circulating estradiol (E2). However, clinical data are conflicting on whether E2 lowers AD risk. One potential contributing factor is APOE. The greatest genetic risk factor for AD is APOE4, a factor that is pronounced in females post menopause. Clinical data suggests that APOE impacts the response of AD patients to E2 replacement therapy. However, whether APOE4 prevents, is neutral or promotes any positive effects of E2 is unclear. Therefore, our goal was to determine whether APOE modulates the impact of E2 on behavior and AD pathology in vivo. To that end, mice that express human APOE3 (E3FAD) or APOE4 (E4FAD) and overproduce Aβ42 were ovariectomized at either 4 months (early) or 8 months (late) and treated with vehicle or E2 for 4 months. In E3FAD mice, we found that E2 mitigated the detrimental effect of ovariectomy on memory, with no effect on Aβ in the early paradigm and only improved learning in the late paradigm. Although E2 lowered Aβ in E4FAD mice in the early paradigm, there was no impact on learning or memory possibly due to higher Aβ pathology compared to E3FAD mice. In the late paradigm, there was no effect on learning/memory and Aβ pathology in E4FAD mice. Collectively, these data support the idea that in the presence of Aβ pathology, APOE impacts the response to E2 supplementation post menopause.